Profession of Future Staff in the Higher Education System Problems of Competence Improvement (Journal of Pedagogical Inventions and Practices, 2023)
This article talks about the tasks in the regulatory and legal documents adopted in the Republic of Uzbekistan, their implementation, the possibilities of developing the professional competence of the pedagogue in preschool educational organizations.